2004
DOI: 10.1055/s-2004-814456
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisse mit dem Contour™-Cochlear-Implant bei Kapselotosklerose

Abstract: None of the Contour patients (n = 7) presented with postoperative facial nerve stimulation. This is in contrast to the majority (4 of 6) of patients being implanted with the straight electrode array. Our results indicate that the use of the Contour array is advantageous in patients being at risk for facial nerve stimulation. In addition intraoperative reports suggest a more reliable insertion of the Contour electrode array in cochlear otosclerosis with partial obliteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Thirty-eight studies had details of preimplantation imaging involving at least 289 patients (2,5,8,9,17,20–53).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-eight studies had details of preimplantation imaging involving at least 289 patients (2,5,8,9,17,20–53).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six studies reported intraoperative adverse events/surgical approach details involving a minimum of 432 patients (2,5,8,9,14,17,19–33,36–61). Scala tympani/round window ossification was noted in at least 84 patients, and further drilling/resection was reported in at least 48 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Battemer et al, 32 using perimodiolar electrode with contacts facing the modiolus is more often associated with reduced FNS than using a straight electrode. 32 In this context, Jaekel et al 34 compared the two types of electrodes and found that none of the patients for whom the perimodiolar electrode was used had FNS. Furthermore, they found that 4/6 patients in whom the straight electrode was used had FNS.…”
Section: Discussionmentioning
confidence: 99%